The State of Cultural Studies Today – Challenges and Opportunities - Hans-Georg Moeller; Mieke Bal; Charles Shiro Inouye; Patrick Colm Hogan; Anne M. Cronin; Catherine Evans; Mark James; Jeffrey Williams; Doris Bachmann-Medick; Paola Bacchetta; Baden Offord; Sue Ballyn; et al. (IAFOR Journal of Cultural Studies)
Short articles with no abstract